KINETICS OF FIR WOOD OXIDATION BY OXYGEN IN AQUEOUS ALKALINE MEDIA - Pervyshina, Ekaterina Petrovna; Tarabanko, Nikolay Valerievich; Tarabanko, Valery Evgenievich; Chernyak, Mikhail Yurievich; Kaygorodov, Konstantin Leonidovich; Chelbina, Yulia Vyacheslavovna; Boyarchuk, Dmitry Valentinovich (Химия растительного сырья, 2016)
Kinetics of fir wood oxidation (Abies sibirica) in aqueous alkaline media were studied by measuring oxygen consumption rates. Oxidation of extracted wood conforms to the kinetics of non-branching chain mechanism. The same mechanism governs the initial stage of non-extracted wood oxidation, but a transition to degenerate branching mode soon occurs. This transition is probably caused by softwood’s low hemicelluloses content and high content of propyl guaiacol lignin units that are prone to condensation involving phenolic hydroxyls. This leads to quick depletion of phenolic and uronic carboxylic groups; chain initiation by oxidizing the respective anions becomes impossible, and degenerate branching takes the lead. It is assumed that inert hydrophobic fir extractives physically shield hydroperoxides responsible for degenerate branching from alkali. This prevents alkali from causing heterolytic hydroperoxide cleavage that does result in chain branching. It is assumed that the catalyst accelerates the reaction of homolytic cleavage of the aforementioned hydroperoxides